Cutis Marmorata Telangiectatica Congenita Associated with Hemiatrophy - Alexander K. C. Leung; Joseph M. Lam; Kin Fon Leong (Case Reports in Pediatrics)
Cutis marmorata telangiectatica congenita is characterized by the presence of a bluish-purple reticulated cutaneous vascular network on the skin intermixed with telangiectasia and occasionally prominent veins at birth. Areas of the skin within the reticulated cutaneous vascular network may be normal, erythematous, atrophic, and, at times, ulcerated. Areas of ulcerations and focal cutaneous and subcutaneous atrophy occasionally occur resulting in body asymmetry. On the other hand, cutaneous and subcutaneous atrophy, extensive and severe enough leading to hemiatrophy, of the entire limb is rare. A search of the English literature revealed only eight documented cases to which we are adding two more cases.